Anagnorisis and narrative incorporation: How significant incidents affect language-learning behavior - Pigott, Julian (Studies in Second Language Learning and Teaching, 2019)
This paper examines how fleeting experiences exert a disproportionately powerful effect on the language learning motivation and behavior of university students. A thematic analysis of interview data is used to show how significant incidents have two principal consequences. The first, anagnorisis, is an immediate, revelatory change in beliefs about language learning. The second, narrative incorporation, is a process through which the memory of the incident and/or its anagnorisis becomes a constituent of self-narratives. It is argued that the significant incident is best understood not as an external influence on motivation, but as a component of the learner’s worldview.